NORMALISASI SEBAGAI SALAH SATU METODE UNTUK MEMBANGUN DATABASE DALAM ERA REVOLUSI TEKNOLOGI SISTEM INFORMASI - Bonnie Soeherman (Journal of Management and Business, 2004)
Information systems and information technology have become a fundamental component of successful business and organization. That's the same important thing as studying marketing, human resource management, operation management, accounting, and the other business components. That's why most managers, entrepreneur, and other business professional have to understand of information system, as it is understand the other business components. This article describes the concept of normalization as one of the methods of building database. This method is recognized as the key success of database's function within companies.